Robust and high resolution hyperpolarized metabolic imaging of the rat heart at 7 t with 3d spectral‐spatial EPI. Issue 4 (20th May 2015) - Miller, Jack J.; Lau, Angus Z.; Teh, Irvin; Schneider, Jürgen E.; Kinchesh, Paul; Smart, Sean; Ball, Vicky; Sibson, Nicola R.; Tyler, Damian J.
Abstract : Purpose: Hyperpolarized metabolic imaging has the potential to revolutionize the diagnosis and management of diseases where metabolism is dysregulated, such as heart disease. We investigated the feasibility of imaging rodent myocardial metabolism at high resolution at 7 T. Methods: We present here a fly‐back spectral‐spatial radiofrequency pulse that sidestepped maximum gradient strength requirements and enabled high resolution metabolic imaging of the rodent myocardium. A 3D echo‐planar imaging readout followed, with centric ordered z ‐phase encoding. The cardiac gated sequence was used to image metabolism in rodents whose metabolic state had been manipulated by being fasted, fed, or fed and given the pyruvate dehydrogenase kinase inhibitor dichloroacetate. Results: We imaged hyperpolarized metabolites with a spatial resolution of 2 × 2 × 3.8 mm 3 and a temporal resolution of 1.8 s in the rat heart at 7 T. Significant differences in myocardial pyruvate dehydrogenase flux were observed between the three groups of animals, concomitant with the known biochemistry. Conclusion: The proposed sequence was able to image in vivo metabolism with excellent spatial resolution in the rat heart. The field of view enabled the simultaneous multi‐organ acquisition of metabolic information from the rat, which is of great utility for preclinical research in cardiovascular disease. Magn Reson Med 000:000–000, 2015. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.Magn Reson Med 75:1515–1524, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance.